A COMPARATIVE STUDY BETWEEN TPS (THINK–PAIR–SHARE) AND TGT (TEAM GAME TOURNAMENT) IN TEACHING WRITING RECOUNT TEXT - Asriani Hasibuan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The purposes of the research are to find out: whether there is a significant comparison between study TPS and TGT in teaching writing recount text at the X Grade Students of SMA Swasta Kampus Padangsidimpuan. In order to achieve the purposes of this research, the researcher carried out the quantitative approach by applying experimental method. The samples are 80 students. Data is measured by using t-test formulation to find the comparison of both methods in teaching writing recount text. Based on the data that have been analyzed, it is found that value is 4.12 meanwhile value is 1.99 at 5% significant level. So, the is bigger than or 4.12 1.99. It means there is a significant comparison between study TPS and TGT in teaching writing recount text at the X Grade Students of SMA Swasta Kampus Padangsidimpuan, in other words the hypothesis is accepted. Keywords : teaching writing, team game tournament, think–pair–share, recount text